Without Our Past? : A Handbook for the Preservation of Canada's Architectural Heritage - Falkner, Ann (Book collections on Project MUSE., 1977)
Using her experience in various government departments and with several successful building conversation projects, Ann Falkner has written this practical handbook for those concerned about preserving heritage structures.